DOES JOB EXPERIENCE AND CUSTOMER ORIENTATIONS CONTRIBUTES TOWARDS SALES PERFORMANCE? CASE OF LIFE INSURANCE - Mulyadi, Dedi; Rismayadi, Budi; Sinaga, Obsatar; Mohamad Yazid, Mohd Faizun (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is evaluate the role of job experience and customer orientations towards the sales performance in insurance industry. Job experience can only be gained over time but it must also come from the employee that willing to explore and take up the challenging works in order to get more knowledge and exposure. Customer orientation at the same time is related on how organization put priority to their customer. Customer orientation is best to be practiced in a service based product. Customer orientation will consider customer needs and wants on top of their marketing and sales strategy. The study is using a sample of 200 life insurance salespersons from selected cities in Indonesia. The results suggested that experience works with customer-oriented selling in making the more experienced salespersons better performers. It was found that more experienced salespersons’ performance is better explained using customer oriented selling. The study contributes by explaining the mechanism for the above relationships. The study also contributes to knowledge by showing that more experience may not be always good for sales performance. The managerial implications of this study lie in explaining those situations where experience can make salespersons more productive.